1994
DOI: 10.1111/j.1399-3011.1994.tb01148.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of locust AKH‐I and its analogues with modifications at the threonine residues

Abstract: A convenient method of synthesis, using a combination of solid and liquid phase methodology, for locust Adipokinetic Hormone-I (AKH-I) and its analogues with modifications at the threonine residues are reported. The N-terminal nonapeptide acid of AKH-I is synthesized in the solid phase using the 2-chlorotrityl chloride resin and the Fmoc/t-Bu strategy. Quantitative cleavage of the nonapeptide acid from the resin, with the tert-butyl type side-chain protection intact, is achieved with a mixture of acetic acid/t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 21 publications
0
5
0
3
Order By: Relevance
“…In such structure-activity bioassays, naturally occurring peptides, or systematically altered analogs were injected into the adult test insect to gather information on dose-response, time-course of the biological response and/or ligand efficacy, for example in vivo assays measuring hyperlipemia in the locust species Locusta migratoria and Schistocerca gregaria [12,14,24,25,30,34,37] or in the sphingid moth M. sexta [10], or measuring hypertrehalosemia in the cockroach species Periplaneta americana [11,13,17] and Blaberus discoidalis [9,26]. There are variations of bioassays where the activity of the enzyme glycogen phosphorylase has been measured in larvae of M. sexta [41], and an in vitro assay was used to monitor the uptake of acetate into fat cells of L. migratoria [29].…”
Section: Introductionmentioning
confidence: 99%
“…In such structure-activity bioassays, naturally occurring peptides, or systematically altered analogs were injected into the adult test insect to gather information on dose-response, time-course of the biological response and/or ligand efficacy, for example in vivo assays measuring hyperlipemia in the locust species Locusta migratoria and Schistocerca gregaria [12,14,24,25,30,34,37] or in the sphingid moth M. sexta [10], or measuring hypertrehalosemia in the cockroach species Periplaneta americana [11,13,17] and Blaberus discoidalis [9,26]. There are variations of bioassays where the activity of the enzyme glycogen phosphorylase has been measured in larvae of M. sexta [41], and an in vitro assay was used to monitor the uptake of acetate into fat cells of L. migratoria [29].…”
Section: Introductionmentioning
confidence: 99%
“…In light of the high fidelity of the three GnRH-related systems (Hansen et al, 2010; Oryan et al, 2018; Wahedi and Paluzzi, 2018), the current study set out to examine for the first time the ligand structure-activity relationship for an insect ACP receptor. This is of utmost importance in order to gain insight on the specific structural features of the ACP system given that extensive studies have been carried out previously on AKH receptors in a variety of species using natural and synthetic analogs of this neuropeptide family (Caers et al, 2012; Fox and Reynolds, 1991; Gäde et al, 2000; Gäde, 1992; Gäde, 1993; Gäde et al, 2016; Keeley et al, 1991; Lee and Goldsworthy, 1996; Lee et al, 1996; Lee et al, 1997; Marco and Gäde, 2015; Marco and Gäde, 2019b; Poulos et al, 1994; Velentza et al, 2000; Ziegler et al, 1991; Ziegler et al, 1998). By examining the activity of a variety of ACP analogs on the activation of the A. aegytpi ACP receptor (ACPR), including single alanine substitutions along with truncated or extended analogs, a few observations can be highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…This might also mean that the hydroxyl group present on the terminal end (Thr 10 ) is less important for peptide-receptor interaction in C. morosus compared with that present on non-terminal residues (Thr 3 , Thr 5 ). In a study with modifications of the Thr residues in Locmi-AKH-I, Poulos et al (1994) demonstrated that in L. migratoria, the hydroxyl group of the Thr 5 of Locmi-AKH-I is important for biological activity, while that of Thr 10 is not. Similarly, in B. discoidalis a single amino acid change at position 10 was well tolerated without much loss in bioactivity (Ford et al, 1988).…”
Section: Hypertrehalosemic Response In C Morosusmentioning
confidence: 99%
“…Two standard methods have been used to investigate AKH ligand-receptor interactions in structureactivity relationship (SAR) studies; the oldest being an indirect in vivo biological assay in which ligands are tested in live animals, and the result of a signal transduction cascade is measured, e.g., the release of lipids/carbohydrates into the hemolymph, or the activation of glycogen phosphorylase. This has been done for AKH bioanalogs and synthetic analogs in locusts (see, for example, Stone et al, 1978;Gäde, 1990Gäde, , 1993Poulos et al, 1994;Goldsworthy et al, 1997), lepidopterans (Fox and Reynolds, 1991;Ziegler et al, 1991Ziegler et al, , 1998Gäde, 2015, 2019) and cockroaches (Gäde, 1986(Gäde, , 1990(Gäde, , 1992Ford et al, 1988;Hayes and Keeley, 1990;Gäde and Hayes, 1995). The second and more recent method of conducting SARs is via a direct in vitro receptor assay; the prerequisite is to have knowledge of the AKH receptor sequence: this is in general (with a few exceptions) only the case for those insects where the whole genome is known.…”
Section: Introductionmentioning
confidence: 99%